Learning qualitative aspects of the ethics of biomedical and psychosocial research program of the Interdisciplinary Center for Studies on Bioethics, University of Chile - Rodríguez, Eduardo (Acta Bioethica, 2012)
This article reflects on the ten years experience of group learning processes and skills acquisition by trainees of the ethics of biomedical and psychosocial research international training program from the Interdisciplinary Center for Studies on Bioethics of the University of Chile, Fogarty Grant R25TW6056. It takes into consideration the role of bioethics in training in its transdisciplinary character.